Governança territorial: diretrizes para o fortalecimento do núcleo gestor da pesca do Rio Canaticu, município de Curralinho - OLIVEIRA, Vivian Marilia da Silva (Universidade Federal do Pará, 2019)
The present research’s main purpose is to present how elements of Territorial Governance may contribute to minimizing the problems of personal, institutional, political and religious nature identified during the process of implementation of the fishing agreements in the Canaticu River, Curralinho municipality. To achieve that, the research has utilized a participant-observation methodology, collecting claims that point to a possible scenery of scarcity of fishing resources, as well as to the above-mentioned problems. A georeferencing was also conducted in the Canaticu River region, using a Garmin GPS, which allowed for the configuration of two maps using the Arc Giz 9.1 program and, finally, a literature review with corresponding discussions. The collecting of data took place between October 2013 and October 2014. The reports were obtained through informal conversations with three local inhabitants, three local community leaders and four representatives of the local civil society and public administration. The reports point to a possible scarcity of fish, as well as other problems, which compromise the process of negotiating these agreements. In that sense, the present research proposes some directives based on territorial governance in order to strengthen the local development of the Canaticu River, as well as a management structure for the agreements through governance workshops